2020
DOI: 10.1109/access.2020.2975893
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Malicious Sliding Windows Similarity Analysis Method for Fast and Accurate IDS Against DoS Attacks on In-Vehicle Networks

Abstract: Controller Area Network (CAN) is a de facto standard of in-vehicle networks. Since CAN employs broadcast communication and a slower network than other general networks (e.g. Ethernet, IEEE802.11), it is inherently vulnerable to Denial-of-Service (DoS) attacks. As a countermeasure against DoS attacks on CAN, a method for detecting a DoS attack using the entropy in a sliding window has been proposed. This method has a good advantage in terms of effectiveness and the small computational overhead. However, this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In 2020, Ohira et al [ 18 ] used the offline learning phase to determine the similarity values for various window sizes. They demonstrated that changing the sliding window size affects the similarity values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Ohira et al [ 18 ] used the offline learning phase to determine the similarity values for various window sizes. They demonstrated that changing the sliding window size affects the similarity values.…”
Section: Resultsmentioning
confidence: 99%
“…However, most IDS have not selected the optimal values for these parameters for intrusion detection. Motivated by this, we investigated into obtaining optimally tuned IDS parameters in order to maximize IDS detection and address the limitations in [ 18 , 19 , 20 , 21 , 22 , 23 ]. We focus on a system model in which ECUs take measurements in real-time and send the results to a service-oriented gateway via different types of CAN buses.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies focus only on the detection accuracy and do not take into account the computational constraints which are crucial in the context of automotive embedded platforms -these constraints are the main focus in our work. In what follows we survey more than twenty-five papers related to the development of in-vehicle IDS, but only a small amount of them, namely [18], [19], [20], [21] and [22] are using embedded development boards. Also, a comparison between invehicle controllers and Android units that are now common in cars is missing from related works.…”
Section: B Related Workmentioning
confidence: 99%
“…The proposed mechanism was implemented and validated on a Raspberry Pi, using the one-class support vector machine and the isolation forest algorithms for intrusion detection. The authors of [22] present a method to detect DoS attacks using the similarity of sliding windows. This method improves prior approaches that detect DoS attacks based on the entropy in a sliding window.…”
Section: B Related Workmentioning
confidence: 99%
“…Meanwhile, the MITM attack occurs in the communication links [151]. In the case of signal jamming, which may lead to an interruption in transmitting the signals, this attack is known as DoS attack [152].…”
Section: Analysis and Impact Of Cyber-attacks Vulnerability On mentioning
confidence: 99%